algebra1

posted by unknown

could you walk-through the steps to solving this problem because I am stuck;
3x-5(3x-7)=2(x+9)+45

Let me know if you have a question in any step.

3x-5(3x-7)=2(x+9)+45
3x-15x+35= 2x+18+45
-12x+35 = 2x+63
-35 -35
-12x= 2x +63-35
-12x= 2x +28
-2x -2x

-12x-2x = 28

-14x= 28
-14x/-14= 28/-14
x = -2

to check just substitute the answer for x to ever x in the original problem.

3x-5(3x-7)=2(x+9)+45

3(-2)-5(3(-2)-7)=2(-2+9)+45
-6 -5 (-6-7)= 2(7)+45
-6-5(-13)=14+45
-6+65=59
59=59 it checks.


You really helped me out. I know see how to work out other problems like this one. Thank you very much!!!

Respond to this Question

First Name

Your Answer

Similar Questions

  1. calc

    What is dy/dx of y=12/12X-y^3 ???? Any idea anyone?
  2. algebra2

    1/3 - 5/6 = 1/X SOLVE 1/3 - 5/6 = 1/X Let's remove the denominators by multiplying by 12X 12X*(1/3) - 12X*(5/6) = 12X*(1/X) Clear the fractions. 4X - 10X = 12 -6X=12 multipy by -1 6X=-12 Divide both sides by 6 6X/6 = -12/6 X = -2 Check …
  3. math

    how do i do x2+12x+32 x2+12x = 14x+32 subtract 14x from each side 14x=32 divide by 2 7x=16 x=16/7, which is 2 and 2/7 ok maybe you typed that question wrong?
  4. bobpursly,

    Is this correct now after i revised it Multiply. 3xy^2(5xy-4x+6y) 3xy^2(5xy)=15x^2y^3 3xy^2(-4x)=-12x^2y^2 3xy^2(6y)=18xy^3 so i get from this 15x^2y^3-12x^2y^2+18xy^3 correct awsome i just thought that the 15x^2y^3-12x^2y^2 should …
  5. algbrea

    3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -12x -28 = 2x -12 -28 =x -40 =x 3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -10x+35=63 -10x=28 x=-2.8 you are both wrong! 3x - 15x + 35 = 2x + 18 + 45 …
  6. Polynomial Fucntion Problem

    Could you help me with the following problem, I don't understand how to do it. Am I suppose to use the linear factorization theorem?
  7. algebra

    24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3-12x check this problem for me please
  8. Math

    Can you correct the errors? 4(x+3)=24 4(3x)=24 12x=24 12x/12= 24/12 X=2 5(x+2)=45 5x+10=45 15x=45 15x/15=45/15 x=3 5+4x=13 5+4x-4x=13-4x 5=9x 5/9=9x/9 5/9= x 56=8(x+3) 56=8x+24 56-24=8x+24-24 32=8x 32/32=8x/32 x=8/32 x=1/4 S/6+3=11
  9. Math

    you know that 8x = 5y you know that 3y=14z since 5 = (5/3)*3, 5y = (5/3)*(3y) so, 5y = (5/3)(3y) = (5/3)(14z) = (70/3)z now you have 5y, which is the same as 8x. You want 12x. since 12 = (3/2)*8, 12x = (3/2)*8x. 12x = (3/2)(8x) = (3/2)(5y) …
  10. Algebra. Please check my answers

    Evaluate a/b+c^d for a=6,b=3,c=4 and d=5 A.42*** B.18 C.82 D.360 What is the simplified form of the expression ?

More Similar Questions